Relasi Guru-Murid dalam Q.S. al-Kahf 66-70: Analisis Tasawuf Ibn ‘Ajībah terhadap Isu Feodalisme Pesantren - Muhammad Rajib Habiburrahman; Norhidayat; Ahmad Mujahid (Jurnal Riset Multidisiplin Edukasi, 2026)
The teacher-student relationship in the Islamic educational tradition, especially in Islamic boarding schools, is often perceived as a hierarchical structure that restricts freedom of thought, especially by groups outside the tradition who do not understand the meaning of khidmah, tabarruk, and adab ta'ẓīm al-'ilm. This study reviews this relationship through the analysis of Q.S. al-Kahf verses 66-70 using Ibn 'Ajībah's approach to Sufism in Al-Baḥr al-Madīd. The research method used is a literature study with content analysis techniques on the interpretation of Ibn 'Ajībah, then compared with literature on pesantren feudalism and anthropological studies on kiai authority. The results of the study show that the stories of Moses and Khidr represent a balanced dialectic between obedience and critical reason, Ibn 'Ajībah distinguishes between the taslīm in the mental realm and the space of questioning in the realm of birth. These findings confirm that the authority of teachers in the Sufistic perspective is not hierarchical dominance, but rather the result of a depth of knowledge and spiritual guidance. Thus, the accusation of feudalism against pesantren needs to be understood more proportionately through the ethical framework of teacher-student relations that opens up a space for dialogue without abandoning manners.